Into the deep : science, technology, and the quest to protect the ocean - Peterson, Christy (Twenty-First Century Books, 2020)
Relays information about the study of the ocean, what oceanographers are learning, and why it is important to understanding the health of the planet. Discusses the role of currents, sea animals, and threats to ocean health. Features full-color photographs, sidebars, a glossary, and resources for further research.